Evaluation of a Model-Driven Proposal to the Development of Groupware Systems - Bibbo, Luis Mariano (2022)
Building groupware is a complex task. This chapter presents the use of the domain-specific language CSSL v2.0 collaborative software system language. CSSL provides simplicity, expressiveness, and precision to model the main concepts of collaborative systems, especially collaborative processes, protocols, and awareness. Models of collaborative systems are created via visual editors that support the concrete syntax of CSSL. According to the MDD methodology, models are independent of the implementation platform and are formally prepared to be transformed. In this implementation, the target of the transformation is a web application that provides a set of basic functions that developers can refine. Evaluation, validation, and verification of the language is performed, determining that the CSSL tools allow developers to solve central aspects of collaborative systems implementation in a simple and reasonable way. The evaluation determined that the CSSL metamodel has low complexity, with semantics strongly associated with UML and with good configuration possibilities.